(untitled) (Italian Journal of Public Health, 2010)
Disasters are an important public health issue with an excessive mortality, high survivor morbidity and functional limitations on daily living. According to the International Strategy for Disaster Reduction (ISDR), the total number of reported people killed between 1991 to 2005 were 960,502 [1]. The total number of reported people affected by a disaster in the same time period was 3.5 billion with economic costs totaling 1193 billion dollars [1]. The number of disasters around the world has increased by more than four times in the last 20 years [2]. Furthermore, the increasing disaster rate has disproportionately affected poorer nations and communities [2]. This has contributed significantly to the downward spiraling effect on the economic, political and public health conditions of several developing nations.